1998
DOI: 10.1183/09031936.98.11061324
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of wheeze and asthma in Nottingham primary schoolchildren 1988-1995

Abstract: The prevalence of asthma in children has increased substantially in many countries in recent decades, but it is not clear how much this trend has continued into the 1990s. This study aimed to estimate the current prevalence of asthma and wheeze in British primary schoolchildren and to determine whether there has been any increase in the prevalence of these conditions since 1988. The prevalence of self-reported wheeze and asthma was measured by parental questionnaire in 22,968 children aged 4-11 yrs attending p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 15 publications
2
31
1
1
Order By: Relevance
“…The present study also found that the gender ratio decreased with age. Decreasing gender ratios have similarly been found in some studies [44][45][46] but increasing ratios have been found in others [47,48]. The 2012 ISAAC summary reported Asia-Pacific prevalences for 6-7 year old children to be 10.8% in boys and 8.2% girls [9].…”
Section: Prevalence Of Childhood Asthma In Beijingmentioning
confidence: 73%
“…The present study also found that the gender ratio decreased with age. Decreasing gender ratios have similarly been found in some studies [44][45][46] but increasing ratios have been found in others [47,48]. The 2012 ISAAC summary reported Asia-Pacific prevalences for 6-7 year old children to be 10.8% in boys and 8.2% girls [9].…”
Section: Prevalence Of Childhood Asthma In Beijingmentioning
confidence: 73%
“…The validity of such a retrospective assessment of the lifetime prevalence of wheeze has been questioned because some surveys of children have failed to show a significant increase in "wheeze ever" with increasing age, and this has been explained by poor parental recall [1,7,8]. Most longitudinal surveys of childhood wheeze have been conducted in late childhood [9,10], or even adults [11], so that poor recall seems likely.…”
mentioning
confidence: 99%
“…It is, therefore, possible that changes in the pattern of amino acid intake arising from an overall increase in the proportion of protein from animal sources [20] may have contributed to the rise in asthma prevalence that has occurred in most developed countries [21]. However, to the current authors9 knowledge, only one previous study has explored the role of plasma amino acids in subjects with asthma and demonstrated that plasma cystine levels were lower in children with previous status asthmaticus as compared to controls [22].…”
mentioning
confidence: 99%